Proteomic analysis of the effects of caffeine in a neonatal rat model of hypoxic‐ischemic white matter damage. (8th April 2022) - Yang, Liu; Yu, Xuefei; Zhang, Yajun; Liu, Na; Li, Danni; Xue, Xindong; Fu, Jianhua
Abstract: Aim: White matter damage (WMD) is the main cause of cerebral palsy and cognitive impairment in premature infants. Although caffeine has been shown to possess neuroprotective effects in neonatal rats with hypoxic‐ischemic WMD, the mechanisms underlying these protective effects are unclear. Herein, proteins modulated by caffeine in neonatal rats with hypoxic‐ischemic WMD were evaluated. Methods: We identified differential proteins and performed functional enrichment analyses between the Sham, hypoxic‐ischemic WMD (HI), and HI+caffeine‐treated WMD (Caffeine) groups. Confirmed the changes and effect of proteins in animal models and determined cognitive impairment via water maze experiments. Results: In paraventricular tissue, 47 differential proteins were identified between the Sham, HI, and Caffeine groups. Functional enrichment analyses showed that these proteins were related to myelination and axon formation. In particular, the myelin basic protein (MBP), proteolipid protein, myelin‐associated glycoprotein precursor, and sirtiun 2 (SIRT2) levels were reduced in the hypoxic‐ischemic WMD group, and this effect could be prevented by caffeine. Caffeine alleviated the hypoxic‐ischemic WMD‐induced cognitive impairment and improved MBP, synaptophysin, and postsynaptic density protein 95 protein levels after hypoxic‐ischemic WMD by preventing the HI‐induced downregulation of SIRT2; these effects were subsequently attenuated by the SIRT2 inhibitor AK‐7. Conclusion: Caffeine may have clinical applications in the management of prophylactic hypoxic‐ischemic WMD; its effects may be mediated by proteins related to myelin development and synapse formation through SIRT2. Abstract : We evaluated the caffeine‐regulated proteins in neonatal rats with hypoxia‐induced WMD and identified 47 differentially expressed proteins. Functional enrichment analysis showed that these proteins were related to myelin development and axon formation. We confirmed in animal models that caffeine increased the expression of myelin basic protein (MBP), synaptophysin (Syp), and postsynaptic density protein 95 (PSD‐95) after WMD by upregulating SIRT2 expression; these increases were attenuated by the SIRT2 inhibitor AK‐7. These findings support the clinical value of caffeine for preventing WMD and indicate that its effect is mediated by proteins related to myelin development and synapse formation.